An Electrochemical Biosensor Platform for Testing of Dehydroepiandrosterone 3‐Sulfate (DHEA−S) as a Model for Doping Materials. Issue 1 (23rd August 2019) - Balaban, Simge; Durmus, Ceren; Aydindogan, Eda; Gumus, Zinar Pinar; Timur, Suna
Abstract: Endogenous steroids such as dehydroepiandrosterone (DHEA) and dehydroepiandrosterone 3‐sulfate (DHEA−S) have commonly used as doping materials by athletes and to date novel techniques are needed for detection of these molecules. In this study, antibody‐based electrochemical biosensor has developed for testing level of the DHEA−S. For this aim, gold surfaces were initially modified with cysteamine (Cys) and then, DHEA−S antibody was immobilized on the surface via glutaraldehyde (GA) as a crosslinking agent. The stepwise modification of electrode surface was monitored by using various electrochemical techniques such as cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). Linear range was determined as 2.5–100 ng/mL DHEA−S using differential pulse voltammetry (DPV) technique, as well. Moreover, repeatability (±S.D.), coefficient of variation (%) and limit of detection (LOD) values were calculated as 0.033, 1.030 and 3.971, respectively. Also, DHEA−S in synthetic serum and urine samples were successfully determined with standard addition method and confirmation analysis were performed with liquid chromatography quadrupole‐time of flight mass spectrometry (LC‐QTOF/MS) system. The selectivity was studied with the addition of some interfering molecules (testosterone, bovine serum albumin (BSA), cholesterol, uric acid, lactic acid, codein (COD), ascorbic acid, DHEA). Consequently, this work is proposed as practical, innovative and cost‐effective technique that can be easily adapted for the miniaturized form for the analysis of other doping substances as well as DHEA−S for the future works. Abstract :